Before and after a natural disaster: Disruption in emotion component of place-identity and wellbeing. (February 2018) - Knez, I.; Butler, A.; Ode Sang, Å.; Ångman, E.; Sarlöv-Herlin, I.; Åkerskog, A.
Abstract: The aim was to investigate relationships between emotion and cognition components of place-identity and wellbeing, before and after a natural disaster. A total of 656 respondents, living near the area of the largest forest and landscape fire in modern times in Sweden, participated in this study. Before the disaster, a positive association was found between place-identity and wellbeing, indicating that the stronger emotions participants evolved to the place, as well as remembered more and thought about the place, the stronger wellbeing they experienced at the site. After the disaster, the strength of this relationship decreased more than twice, accounted for by the weakening of the emotion-wellbeing link. Accordingly, participants almost lost their emotional bond to the area but maintained their memories and thoughts about the site intact and, by that, their positive wellbeing associations with the location. This indicates tentatively the phenomenon of post-traumatic growth, type of resilience involving operations of cognitive appraisal. Highlights: Before disaster – the stronger place-identity the stronger wellbeing. After disaster – participants lost their emotional bond to place. After disaster – association between cognitive bond and wellbeing maintained.